Survival and Development of Striacosta albicosta (Smith) (Lepidoptera: Noctuidae) Immature Stages on Dry Beans, non-Bt, Cry1F, and Vip3A Maize - G. Montezano, Débora (Insects, 2019)
Striacosta albicosta is a crop pest that causes economic damage in the United States and Canada. Only maize and dry beans are shown to be suitable hosts, since larval development is incomplete on other hosts. The objective of this study was to describe the developmental parameters of immature stages of S. albicosta feeding on dry beans, non-Bt, Cry1F, and Vip3A maize. For Vip3A, mortality was 100% after 24 h. Larvae feeding on non-Bt maize had the highest larval survival (70.6%) compared to the other hosts. Maize expressing Cry1F had higher survival (31.3%) than dry beans (26.0%). Larvae feeding on dry beans had a significantly faster total development time (74.8 days), compared to 92.5 days for non-Bt and 96.2 days for Cry1F. All larvae developed through seven instars. Pupae from larvae that had fed on non-Bt maize were significantly heavier than pupae from other hosts. An understanding of S. albicosta immature development on various host plants is needed to improve recommendations for effective scouting, treatment timing, and economic thresholds. Differential development can result in an extended adult emergence period, and possibly result in assortative mating between Bt susceptible and resistant populations, which violates the assumption of random mating necessary for current resistance management strategies for Bt maize. Therefore, understanding the impact of host plant and transgenic traits on aspects of pest biology will aid in developing effective integrated pest management and insect resistance management strategies for this pest.